2020
DOI: 10.1002/cam4.2826
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported symptom burden as a prognostic factor in treatment with first‐line cetuximab plus chemotherapy for unresectable metastatic colorectal cancer: Results of Phase II QUACK trial

Abstract: Background It remains unclear whether patients’ self‐perceptions of symptoms at baseline clinically impact the prognostic relevance, treatment efficacy, or toxicity profiles in metastatic colorectal cancer (mCRC) patients treated with the first‐line cetuximab and standard chemotherapy. Methods The data were collected from a prospective trial that assessed the relationships between quality of life (QOL), treatment efficacy, and adverse events (AEs). Results The analysis of 137 mCRC patients revealed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…38,39 In keeping with prior work, the results of the current study have demonstrated an association between a greater number of sites of metastasis, increased physical symptom burden, and worse QOL. 40 We also found a novel relationship between PROs and patient baseline CEA levels. These relationships suggest a potential underlying link between patients' tumor burden and their physical symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…38,39 In keeping with prior work, the results of the current study have demonstrated an association between a greater number of sites of metastasis, increased physical symptom burden, and worse QOL. 40 We also found a novel relationship between PROs and patient baseline CEA levels. These relationships suggest a potential underlying link between patients' tumor burden and their physical symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, 55 patients (40%) reported "very much" or "quite a bit" on at least one of the corresponding symptom items of the EORTC QLQ-C30. 13 High compliance rates for the EORTC QLQ-C30 questionnaire were maintained throughout the study period (i.e., 97.9% at baseline, 97.0% at 4 weeks, and 81.1% at 24 weeks).…”
Section: Status Of Agreement Between Patient and Physician Reportinmentioning
confidence: 86%
“…Although the substantial variability between physician and patient assessments of symptomatic AEs may depend on specific cancer types and treatment, no prior studies have directly compared patients’ and physicians’ reports of symptomatic AEs in mCRC patients treated with first‐line cetuximab plus chemotherapy. In addition, we and others have previously shown that baseline patient‐reported symptoms are predictors of survival in CRC, 13–16 but the prognostic value of the disagreement between patient‐ and physician‐reported outcomes for symptomatic AEs during chemotherapy has not yet been determined.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations